2009
DOI: 10.1177/0269215508096760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intradialytic exercise training on health-related quality of life indices in haemodialysis patients

Abstract: The results demonstrated that intradialytic exercise training improves both physical functioning and psychological status in haemodialysis patients, leading to an improvement of patients' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
171
1
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(206 citation statements)
references
References 42 publications
16
171
1
18
Order By: Relevance
“…There was a significant change in MCS between the exercise and the comparison group after the PRT program in this study, although not all previous studies supported this finding (Jang & Kim;Ouzouni et al, 2009). Such disagreement is thought to stem from the fact that the improvement in physical fitness is not the only influencing factor for MCS -the participants' physical fitness and their MCS level before the exercise program, as well as how the PRT was facilitated, also affect MCS.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…There was a significant change in MCS between the exercise and the comparison group after the PRT program in this study, although not all previous studies supported this finding (Jang & Kim;Ouzouni et al, 2009). Such disagreement is thought to stem from the fact that the improvement in physical fitness is not the only influencing factor for MCS -the participants' physical fitness and their MCS level before the exercise program, as well as how the PRT was facilitated, also affect MCS.…”
Section: Discussioncontrasting
confidence: 61%
“…Page and Ellenbecker's study (2003) concluded that the muscle strength of older adults increased by 6 to18% after PRT using elastic bands, and the findings of this study support this, as the exercise group showed a 13% increase in leg muscle strength. A 24-week PRT and lowintensity aerobic exercise program for patients on HD showed the leg muscle strength and physical fitness of those in an exercise group increased significantly (Ouzouni, Kouidi, Sioulis, Grekas, & Deligiannis, 2009), suggesting that PRT is more effective than aerobics exercises in improving muscle strength.…”
Section: Discussionmentioning
confidence: 98%
“…In-depth Review Fleck et al [53] , 2007 Discussion Carver et al [57] , 1995 Review Blinkhorn [61] , 2012 Review O'Connor et al [64] , 2012 Review Catania et al [65] , 2013 Report Quantitative Study design Questionnaire used Mapes et al [8] Longitudinal KDQOLSF-36 Kao et al [13] , 2009 Cross sectional SF-36 Abraham et al [14] , 2008 Case control, follow up WHOQOL-BREF Kimmel et al [15] , 2008 Prospective Satisfaction with Life Scale (SLS), McGill QOL, Single item Patel et al [16] , 2002 Prospective McGill QOL, Beck Depression Griva et al [17] , 2009 Cross sectional SF-36 Elder et al [19] , 2008 Cross sectional, case mix KDQOLSF-36 Sanner et al [20] , 2002 Cross sectional SF-36, Nottingham Health Profile Tondra [22] , 2014 Conceptual Framework, CS Quality of Life Index Dialysis, Mingardi et al [23] , 1999 Prospective SF-36 Seica et al [24] , 2009 Cross sectional SF-36, KDQOLSF-36 Bakewell et al [25] , 2002 Longitudinal /intervention KDQOLSF-36 Theofilou [26] , 2012 Cross sectional/ Observational WHOQOL-BREF, GHQ-28 Kim et al [28] , 2013 Cross sectional KDQOLSF-36 White et al [29] , 2002 Retrospective cohort SF-36 Painter et al [32] , 2000 Experimental/Intervention SF-36 Ouzouni et al [33] , 2009 RCT SF-36, Quality of Life Index Agakhani et al [34] , 2012 Case control/comparative SF-36 Hegazy et al [35] , 2013…”
Section: Resultsmentioning
confidence: 99%
“…[22,25] , influence of dialysis care practice [27] , self-efficacy, treatment satisfaction [28] , pre-dialysis clinic attendance [29] , exercise [30] . Intervention such as dietary counseling [34,35] , individual/group counselling [14,36,37,40] , education on regular exercise [31][32][33] , physical and psychological rehabilitation interventions, palliative care to manage symptoms [38] , and cognitive behavior therapy to reduce depression [39] Inverse association of factors with QOL More worries and higher depression [13] , ignorance about the basic facts of one's disease [14] , Pain, financial constraints [14] , psychological and spiritual factors [15] , emotional impact, physical impact on daily living, role of religious and spiritual beliefs [16] , beliefs related to illness and treatment [17] , anxiety, depression, suicidal ideation, grief of loss of kidney, self-image selfesteem [18] , sleep quality [19] , sleep related breathing disorders [20] , as well as erectile dysfunction, patient satisfaction with care, depressive aspects, symptom burden, and perception of intrusiveness of illness [21] , female gender [22][23][24]26] , ethnicity [25] , older age [26] , less education [24,26] , poor nutritional status [25] and divorced marital status, Illness and treatment beliefs [17] , work and Symptom domain [25] No or very weak association of fa...…”
Section: Discussionmentioning
confidence: 99%
“…While 98.6% of U.S.A. nephrologists who were present at the Meeting of the American Society of Nephrology in 2001 have recognized the benefits of PA, only 28.5% were prescribing exercises to their patients 30 , which draws attention to the investigation of the reasons why this prescription or referral for the practice of PA is not being properly considered. Studies have shown the benefits of PA on the relief of depressive and psychological well-being symptoms 31,32 , with reduction of the BDI score after a program of intra-dialysis aerobic exercises in patients undergoing HD 33 , as well as the Brazilian Society of Nephrology itself recommends the practice of regular physical activity as a non-pharmacological measure for the control of CKD 34 . It was observed, in this study, that most part of the sedentary consisted of subjects who used to be inactive before the four years of treatment.…”
Section: Discussionmentioning
confidence: 99%